EFEKTIVITAS APLIKASI ZOOM DALAM E-LEARNING TERHADAP MINAT BELAJAR PESERTA DIDIK SEKOLAH DASAR - Fitria Husna Fadhilah; Sekar Dwi Ardianti; M. Syafruddin Kuryanto (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to determine the effectiveness of the Zoom application on students' learning interest at elementary schools. This study used an experimental method with a one-group pretest-posttest design. The research subjects were fifth-grade students of SD 2 Garung Kidul, selected through saturated sampling. The variables included learning interest and the Zoom application. Data were collected through observation and questionnaires and analyzed using paired sample t-test and N-Gain test with SPSS IBM 21. The results showed that the paired sample t-test produced a Sig. (2-tailed) of 0.00, which was smaller than 0.05, indicating that Ho was rejected and Ha accepted, meaning there was a significant difference between pretest and posttest scores. Furthermore, the N-Gain score showed an average percentage of 60%, with a minimum of 1.6% and a maximum of 100%, indicating that the Zoom application effectively improved students' learning interest in e-learning at elementary schools. Keywords: , ,